A Self‐Administered Method of Acute Pressure Block of Sciatic Nerves for Short‐Term Relief of Dental Pain: A Randomized Study. Issue 8 (8th January 2014) - Wang, Xiaolin; Zhao, Wanghong; Wang, Ye; Hu, Jiao; Chen, Qiu; Yu, Juncai; Wu, Bin; Huang, Rong; Gao, Jie; He, Jiman
Abstract: Objectives: While stimulation of the peripheral nerves increases the pain threshold, chronic pressure stimulation of the sciatic nerve is associated with sciatica. We recently found that acute pressure block of the sciatic nerve inhibits pain. Therefore, we propose that, the pain pathology‐causing pressure is chronic, not acute. Here, we report a novel self‐administered method: acute pressure block of the sciatic nerves is applied by the patients themselves for short‐term relief of pain from dental diseases. Design: This was a randomized, single‐blind study. Setting: Hospital patients. Patients: Patients aged 16–60 years with acute pulpitis, acute apical periodontitis, or pericoronitis of the third molar of the mandible experiencing pain ≥3 on the 11‐point numerical pain rating scale. Interventions: Three‐minute pressure to sciatic nerves was applied by using the hands (hand pressure method) or by having the patients squat to force the thigh and shin as tightly as possible on the sandwiched sciatic nerve bundles (self‐administered method). Outcomes: The primary efficacy variable was the mean difference in pain scores from the baseline. Results: One hundred seventy‐two dental patients were randomized. The self‐administered method produced significant relief from pain associated with dental diseases ( P ≤ 0.001). The analgesic effect of the self‐administered method was similar to that of the hand pressure method. Conclusions: The self‐administered method is easy to learn and can be applied at any time for pain relief. We believe that patients will benefit from this method.